Physiological responses to an acute bout of sprint interval cycling - Freese, E. C.; Gist, N. H.; Cureton, K. J. (The Journal of Strength and Conditioning Research, 2013)
Sprint interval training has been shown to improve skeletal muscle oxidative capacity, VO2max, and health outcomes. However, the acute physiological responses to 4-7 maximal effort intervals have not been determined. To determine the VO2, cardiorespiratory responses, and energy expenditure during an acute bout of sprint interval cycling (SIC), health, college-aged subjects, 6 men and 6 women, completed 2 SIC sessions with at least 7 days between trials. Sprint interval cycling was performed on a cycle ergometer and involved a 5-minute warm-up followed by four 30-second all-out sprints with 4-minute active recovery. Peak oxygen uptake (ml/kg/min) during the 4 sprints were 35.3 ± 8.2, 38.8 ± 10.1, 38.8 ± 10.6, and 36.8 ± 9.3, and peak heart rate (b/min) were 164 ± 17, 172 ± 10, 177 ± 12, and 175 ± 22. We conclude that an acute bout of SIC elicits submaximal VO2 and cardiorespiratory responses during each interval that are above 80% of estimated maximal values. Although the duration of exercise in SIC is very short, the high level of VO2 and cardiorespiratory responses are sufficient to potentially elicit adaptations to training associated with elevated aerobic energy demand.